Plasticizer contamination in the urine and hair of preschool children, airborne particles in kindergartens, and drinking water in Hong Kong. (15th February 2021) - Li, Na; Ying, Guang-Guo; Hong, Huachang; Tsang, Eric Po Keung; Deng, Wen-Jing
Abstract: Common plasticizers and their alternatives are environmentally ubiquitous and have become a global problem. In this study, common plasticizers (phthalates and metabolites) and new alternatives [bisphenol analogs, t -butylphenyl diphenyl phosphate (BPDP), and bisphenol A bis(diphenyl phosphate) (BDP)] were quantified in urine and hair samples from children in Hong Kong, drinking water (tap water/bottled water) samples, and airborne particle samples from 17 kindergartens in Hong Kong. The results suggested that locally, children were exposed to various plasticizers and their alternatives. High concentrations of BPDP and BDP were present in urine, hair, tap water, bottled water, and air particulate samples. The geometric mean (GM) concentrations of phthalate metabolites in urine samples (126–2140 ng/L, detection frequencies < 81%) were lower than those detected in Japanese and German children in previous studies. However, a comparison of the estimated daily intake values for phthalates in tap water [median: 10.7–115 ng/kg body weight bw/day] and air particles (median: 1.23–7.39 ng/kg bw/day) with the corresponding reference doses indicated no risk. Bisphenol analogs were detected in 15–64% of urine samples at GM concentrations of 5.26–98.1 ng/L, in 7–74% of hair samples at GM concentrations of 57.5–2390 pg/g, in 59–100% of kindergarten air samples at GM concentrations of 43.1–222 pg/m 3, and in 33–100% of tap water samples at GM concentrations of 0.90–3.70 ng/L. A significant correlation was detected between the concentrations of bisphenol F in hair and urine samples ( r  = 0.489, p  < .05). The estimated daily urinary excretion values of bisphenol analogs suggest that exposure among children via tap water intake and airborne particle inhalation in kindergartens cannot be ignored in Hong Kong. Graphical abstract: Image 1 Highlights: Local Hong Kong children were exposed to phthalates, bisphenol analogs and OPEs. BPDP and BDP were detected in urine/hair, tap/bottled water and air particles. Back-calculated EDEu of bisphenol analogs were 2.15–36.5 ng/kg tw/d. Tap water and air particle exposure pathway cannot be ignored for bisphenol analogs.